Public health emergency and psychological distress among healthcare workers: a scoping review - Jennifer Palmer; Michael Ku; Hao Wang; Kien Crosse; Alexandria Bennett; Esther Lee; Alexander Simmons; Lauren Duffy; Jessie Montanaro; Khalid Bazaid (BMC, 2022)
Abstract Background Pandemics and natural disasters are immensely stressful events for frontline healthcare workers, as they provide patient care to a population undergoing the impacts of the disaster while experiencing such impacts to their personal lives themselves. With increased stressors to an already demanding job, frontline healthcare workers are at a higher risk of adverse effects to their mental health. The current COVID-19 pandemic has already shown to have had significant impact on the mental health of healthcare workers with increased rates of burnout, anxiety and depression. There is already literature showing the utility of individual programs at improving mental health, however, interventions at the organizational level are not well explored. This scoping review aims to provide an overview and determine the utility of a systematic review of the current body of literature assessing the effectiveness of mental health interventions at the organizational level for healthcare workers during or after a public health emergency. Methods Electronic databases such as Medline on OVID, CENTRAL, PsycINFO on OVID and Embase on OVID were searched. A targeted search of the grey literature was conducted to identify any non-indexed studies. The population, concept and context approach was used to develop the eligibility criteria. Articles were included if (1) they assessed the impact of interventions to improve wellbeing or reduce the distress on healthcare personnel, first responders or military actively providing medical care; (2) provided quantitative or qualitative data with clearly defined outcomes that focused on established mental health indicators or qualitative descriptions on distress and wellbeing, validated scales and workplace indicators; (3) focused on organizational level interventions that occurred in a public health crisis. Results The literature search resulted in 4007 citations and 115 potentially relevant full-text papers. All except 5 were excluded. There were four review articles and one experimental study. There were no other unpublished reports that warranted inclusion. Conclusions There is a distinct lack of research examining organizational interventions addressing mental resilience and well-being in healthcare workers in disaster settings. A systematic review in this area would be low yield. There is a clear need for further research in this area.